Law, space, and the vehicular environment : pavement and asphalt - Marusek, Sarah (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book examines the paved road as a liminal space and legal frontier for enlivened, everyday struggles over property, power, and place/definition. Through pavement itself and the pavement-based practices of pavementalities and pavementeering, the road is legally framed as a place for movement. Paved terrain is a site of dynamism between law and place that engenders the road as legal metaphor by calling forth the kinetic notion of jurisprudence in which law can be understood through the fluidity of everyday life. In Western, and particularly American society, roads are a material locus of governance, in which rights of way are determined, communicated and enforced. However, roads also constitute a site of resistance or disruption, beyond regulation. Addressing phenomena such as travel, political protest, public memory, and community governance, this book explores paved medium of asphalt as a complex surface for legality that constitutively frames order against disorder involving jurisdiction tensions, property ownership, and cultural identities in vehicular environments. The target audience of this book are those students and scholars who consider how law works in society whether through frameworks of (auto)mobility and legal geography or through the interdisciplinary approaches of legal semiotics, legal culture, and/or new materialism"--
Pavement -- Pavementalities -- Pavementeering.
"Routledge Focus"--PDF image of cover.
Keywords: Space in economics; Roads; SOCIAL SCIENCE / Sociology / Urban; SOCIAL SCIENCE / Human Geography; LAW / Environmental